2014
DOI: 10.1038/jcbfm.2014.142
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exercise Stress Reveals Cerebrovascular Benefits Associated with Moderate Gains in Cardiorespiratory Fitness

Abstract: Elevated cardiorespiratory fitness improves resting cerebral perfusion, although to what extent this is further amplified during acute exposure to exercise stress and the corresponding implications for cerebral oxygenation remain unknown. To examine this, we recruited 12 moderately active and 12 sedentary healthy males. Middle cerebral artery blood velocity (MCAv) and prefrontal cortical oxyhemoglobin (cO(2)Hb) concentration were monitored continuously at rest and throughout an incremental cycling test to exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 15 publications
3
41
3
Order By: Relevance
“…However, no comparative data exist for resistance‐trained individuals (to our knowledge). Despite the lack of an observable difference in resting measures, improved CO 2 reactivity has been reported in individuals with greater cardiorespiratory fitness (Bailey et al., ; Murrell et al., ) and larger increases in MCAv and prefrontal cortical oxygenation during the transition from low to moderate aerobic exercise (Brugniaux et al., ). These data indicate an improvement in vascular function in response to stressors associated with endurance exercise – for example, increases in blood flow in response to cortical activation and alterations in arterial CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, no comparative data exist for resistance‐trained individuals (to our knowledge). Despite the lack of an observable difference in resting measures, improved CO 2 reactivity has been reported in individuals with greater cardiorespiratory fitness (Bailey et al., ; Murrell et al., ) and larger increases in MCAv and prefrontal cortical oxygenation during the transition from low to moderate aerobic exercise (Brugniaux et al., ). These data indicate an improvement in vascular function in response to stressors associated with endurance exercise – for example, increases in blood flow in response to cortical activation and alterations in arterial CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Brugniaux et al. () showed that the fitness effect for cerebral blood velocity was only apparent during incremental cycling exercise, but not at rest. With this in mind, reduced TFA phase at 0.10 Hz and elevated TFA normalized gain at 0.05 Hz have also been reported with driven oscillations in MAP during moderate exercise with old versus young adults, while these values were also comparable at rest (Smirl et al.…”
Section: Discussionmentioning
confidence: 99%
“…), while higher cardiorespiratory fitness (CRF) has been shown to improve cerebral blood velocity during exercise (Brugniaux et al. ), as well as cerebrovascular reactivity to carbon dioxide (Bailey et al. ; Barnes et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Brugniuax et al . ), dependent on the magnitude of hyperventilation‐induced hypocapnia, or lack thereof (Smith et al . ).…”
Section: Introductionmentioning
confidence: 99%